Changes in bird populations at the Santa Inés Agroecological farm, Zamorano University, Honduras - Giron F., Marilis E. (Zamorano: Escuela Agrícola Panamericana, 2025)
The study aimed to identify bird species with temporal trends, evaluate the relationship between these trends and climate variability, and determine differences between resident and migratory birds. For 7 years, ornithologist Oliver Komar counted birds at Zamorano University's agroecological farm. Time series decomposition and regression analysis were applied to identify temporal trends for 88 bird species. Subsequently, regression and contingency table analysis were employed to examine the relationships between migratory and resident bird species with temperature and precipitation. Temporal trends were significant for 51 species (58%), with 41 (47%) declining and 10 (11%) increasing. The magnitude of declines averaged 59% while increases averaged 155%. Temperature had a negative effect on 18 species (20%) and a positive effect on six (7%). Precipitation negatively affected 10 bird species (11%) and positively two (2%). Temporal declines were proportionally more frequent for residents, but the magnitude of the declines was greater for migrants. Temperature was more negatively correlated with migrants. Differences between migrants and residents with respect to precipitation were inconclusive. In conclusion, (1) more bird species are declining than are increasing on the farm, which will eventually erode biodiversity; (2) as biodiversity declines the farm will become more vulnerable to climate change, agricultural pests, and invasive species. Furthermore, (3) the ecosystem services provided by migratory birds are diminishing. Recommendations include using non-parametric methods and different time scales to analyze the effects of climate change on birds, investigating the relationships between feeding guilds and other factors that affect birds, and developing a biodiversity conservation plan for the farm.